DEMOCRATIC INSTITUTIONS AND CIVIL TOLERANCE AS A CONSENSUS METHOD FOR CONFLICTS’ RESOLUTION - Біденко, Ю.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The basic theories of democracy are considered in a correlations with the concepts of tolerance and civil society. There says that democracy promotes evaluation of a conflict as non-zero-sum games. Also, using Ukrainian example, the author shaws high potential for a socio-political conflict in transitional societies with unpredictable electoral cycle and weak values of tolerance.